Occupational Stress of the Teacher and its Relation to Locus of Control "Field Study on A Sample of Teachers of the First Grade of Basic Education in Lattakia City" - جناد, روعة; جديد, لبنى; جراد, ريم (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research aimed to explore the level of occupational stress of the teacher, and to know if there is a correlation between the occupational stress and the locus of control, and the differences in the sample according to the gender and years of Experience variable. A sample of the research consisted (130) teachers(male and female) from teachers of the first grade of basic education in Lattakia city. The sample was randomly drawn, and the researcher followed the descriptive methods, and used the occupational stress scale and it consists of four dimensions of preparation by "Youssef Abdel Fattah Mohamed" and scale of (Rotter, 1966 Internal / External locus of control) Which was Arabized and re-codified to the Arab community Kafafi (1982), after confirming their sincerity and persistence in the local environment. The research arrived the following results:- The level of occupational stress of teachers in the members of the study sample it came in the middle level.- There is a positive correlation between the occupational stress and the locus of control with first grade of basic education teachers in Lattakia city.- There are differences of statistical reference in the level of occupational stress with first grade of basic education teachers according to gender variable for females.- There are no differences of statistical reference in the locus of control with first grade of basic education teachers according to the gender variable (males, females).-There are statistically significant differences in the occupational stress with first grade of basic education teachers according to the variable number of years of experience for the benefit of the experienced (10) years and more.- There are no differences of statistical reference in the locus of control with first grade of basic education teachers according to the variable number of years of experience